Zeolite P from kaolin via hydrothermal method - Apiluck Eiad-ua; Phanwasa Amnaphiang; Panuruj Asawaworarit; Nongluck Houngkamhang; Nuwong Chollacoop; Masayoshi Fuji (My University, 2018)
Zeolite P has been successfully synthesized from natural kaolin via two step hydrothermal process. The natural kaolin from Lampang, Thailand was studied for this research. In first hydrothermal, kaolin was mixed with sodium hydroxide solution at 200 oC for different reaction times from 3 – 5 hours, respectively .Sodium hydroxide and hydrochloric acid were added into the mixture to adjust their pH before they were formed into gel. Second hydrothermal process, the gel was kept of 90 oC for 3 days to obtain zeolite P. Synthesized zeolite P was characterized by X-ray diffraction (XRD) for identification the type and crystallization. Besides, the morphology was characterized by scanning electron microscopy )SEM.( The functional group was characterized by Fourier-transform infrared spectroscopy (FTIR). From this study, it was found that the increasing of reaction time in first hydrothermal activation and hydrochloric acid concentration lead to the high quality of zeolite P
Keywords: Hydrochloric acid; Sodium hydroxide; Hydrothermal Synthesis; Clay minerals and soil interactions